PENGARUH PENGGUNAAN TERAPI MUSIK DAN AROMATERAPI PADA PERAWATAN SPA TERHADAP TINGKAT RELAKSASI PELANGGAN ASNITA SALON SPA DAN BEAUTY CARE KABUPATEN PASAMAN BARAT - Alasta, Salsabilla Saqina Putri; Astuti, Murni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research is motivated by the increasing need for relaxation in modern society as an effort to reduce stress and maintain mental health. SPA treatments, especially with the integration of music therapy and aromatherapy, are believed to provide optimal physical and psychological benefits. However, the effectiveness of applying these two methods to increase customer relaxation still requires empirical evidence. This study aims to analyze the effect of music therapy and aromatherapy in SPA treatments on the level of relaxation of Asnita Salon SPA & Beauty Care customers in West Pasaman Regency. The research method used is quantitative with a correlational analytical design. The population of this study were Asnita Salon SPA & Beauty Care customers in West Pasaman Regency. Sampling using a purposive sampling technique totaling 64 respondents aged 20–55 years selected from salon customers, with data collection techniques using a questionnaire via Google Form and measured using a Likert scale that has been tested for validity and reliability. The data analysis technique of this study is data tabulation and data description. The analysis requirements tests carried out are normality tests, linearity tests and multiple linear regression tests to test the research hypothesis. The research results show that 1) the music therapy variable is in the very good category with a percentage of 84.72%, 2) the aromatherapy variable is also in the very good category with a percentage of 85.23%, 3) the client's relaxation level reached 85.50%. These findings indicate that both independent variables have a significant positive impact on increasing relaxation. 4) the contribution of the Music Therapy and Aromatherapy variables to the Relaxation Level is 70.4%. The remaining 29.6% variation in the Relaxation Level is influenced by other variables not included in this study.Keywords: Music Therapy, Aromatherapy, SPA Treatment, Relaxation Level.